Fenomena Ilmu Kebatinan Masyarakat Jawa di Desa Bandar Setia, Kecamatan Percut Sei Tuan. - Muhammad Fadli; Yusda Novianti; Ayu Febryani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to describe the phenomenon of mysticism in Javanese society in Bandar Setia Village, Percut Sei Tuan District. The research method used is ethnography, while the technique, the data is done by observation and in-depth interviews. Three informants were appointed as mystical therapy. The results showed that the phenomenon of mysticism has long developed in the village of Bandar Setia which is interpreted as a concept of belief to get closer to the Creator. The concept of mysticism focuses on awakening the sense of awakening to feel every natural occurrence, magical phenomena. To acquire mysticism, one has to do penance such as fasting and other special rituals. The benefits of mysticism are not only as a means of getting closer to the creator but also being able to provide supernatural abilities for its users. This ability is often used to help people related to life problems they face. Mysticism is a part of cultural identity that needs to be preserved as noble values because mysticism is one of the products of local wisdom in the Javanese community of Bandar Setia.